The fabrication of porcelain ceramic via Wet casting technique - Meor Syazalee Sha @ Meor Sha (Universiti Malaysia Perlis, 2008)
Porcelain ceramic which composed of ball clay, kaolin, silica and feldspar were fabricated and investigated to study the effect of sintering temperature on mechanical properties. Two types of parameter were used in these projects which were different composition of raw material and sintering temperature. Three different compositions of raw materials were used which were composition A, B and C. The wet mixture then was sintered at 1200°C and 1300°C for 3 hours soaking time at 5°C/min for heating rate. The compression test and characterization of the sample such as the porosity, density, shrinkage and weight loss were carried out in order to determine the properties of the final product. The sample were also been analyzed using Scanning Electron Microscope (SEM) to capture the sample microstructure. From all experiment and testing, it is found that by increasing the sintering temperature, the compression strength, bulk density, and shrinkage were increased and at the same time reducing the percent of porosity of the porcelain ceramic.